Penyihir Dalam The Scarlet Letter Karya Nathaniel Hawthorne: Tinjauan Ekofeminisme - Juliasih Juliasih (Humaniora, 2008)
The term witchcraft can have positive or negative connotations depending on the cultural context. Amongst Puritans it has historically been associated with evil and the devil. Some people think when people say the word witch or witchcraft they think it is evil and traditionally stereotyped as being female. Ecofeminists who self-identify as “witches” see it as beneficent and morally positive.